JALANI GAYA HIDUP BERSIH DAN SEHAT UNTUK MENCEGAH PENULARAN UNTUK MENCEGAH PENULARAN VIRUS COVID-19 - Dalimunthe, Khodijah Tussolihin; Nauli, Mutiara (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
Clean and healthy living behavior (PHBS) is a behavior that is carried out on self-awareness so that family members can help themselves. In addition, PHBS is a step that must be taken to achieve optimal health degrees for everyone. PHBS plays an active role in preventing the transmission of COVID-19 which causes many human deaths in the world. service that aims to convey information to the community, especially the Namo Ukur Village, Langkat Regency to remain obedient to government rules and maintain personal and family hygiene by implementing clean and healthy living behaviors. This type of service is health promotion using the lecture method and distributing masks to the community. Service activities provide good results for the community. It can be seen the enthusiasm and enthusiasm of the community in asking questions when delivering the material. t is hoped that this activity can increase knowledge and increase public awareness if a clean and healthy lifestyle is very important to prevent the transmission of COVID-19.